2018
DOI: 10.3847/1538-4357/aad32e
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Large Extreme-ultraviolet Late Phase Powered by Intense Early Heating in a Non-eruptive Solar Flare

Abstract: We analyzed and modeled an M1.2 non-eruptive solar flare on 2011 September 9. The flare exhibits a strong late-phase peak of the warm coronal emissions (∼3 MK) of extreme-ultraviolet (EUV), with peak emission over 1.3 times that of the main flare peak. Multiple flare ribbons are observed, whose evolution indicates a two-stage energy release process. A non-linear force-free field (NLFFF) extrapolation reveals the existence of a magnetic null point, a fan-spine structure, and two flux ropes embedded in the fan d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
2
11
0
Order By: Relevance
“…Also, such time delays in peak emissions of light curves of strong eruptions (occurred from ARs for example Vemareddy & Zhang (2014)) are quite smaller (≈ 10min). Though studies like (Liu et al 2015;Dai et al 2018) also observed the large time delays between peak emissions in EUV light curves of AR during confined flare events, we need more comparative studies between strong and weak eruptive ARs to verify our result.…”
Section: Light Curvessupporting
confidence: 52%
See 1 more Smart Citation
“…Also, such time delays in peak emissions of light curves of strong eruptions (occurred from ARs for example Vemareddy & Zhang (2014)) are quite smaller (≈ 10min). Though studies like (Liu et al 2015;Dai et al 2018) also observed the large time delays between peak emissions in EUV light curves of AR during confined flare events, we need more comparative studies between strong and weak eruptive ARs to verify our result.…”
Section: Light Curvessupporting
confidence: 52%
“…et al 2012) and its wider peak is accounted for by different cooling timescales of the heated coronal loops. A dip in the AIA 171 profile during main phase reconnection is mainly due to the hot reconnection loops which are opaque to the cooler passband of AIA 171 (Dai et al 2018). Later these loops slowly started to appear in AIA 171 and warm coronal emission peaks at 2:52UT on January 7, which is mainly due to the long cooling process of the late-phase loops as proposed in Liu et al (2013).…”
Section: Light Curvesmentioning
confidence: 72%
“…Relation between energy in nonthermal electrons E nth and peak thermal energy E th as derived by different studies and methods. Shown are the logarithmic mean ratios, E nth /E th , and the correlation coefficient of the logarithms of the two quantities, C. heating rate for the late-phase loops may be at least as high as for the main flaring loops (Dai et al 2018).…”
Section: Additional Flare Energetics Not Considered So Farmentioning
confidence: 99%
“…This component, located in distinct loop systems, implies additional heating requirements. Just considering radiative losses in EUV, it has been shown that the EUV late phase can be up to four times more energetic than the main phase (Liu et al 2015), and numerical modeling suggests that the peak heating rate for the late-phase loops may be at least as high as for the main flaring loops (Dai et al 2018).…”
Section: Additional Flare Energetics Not Considered So Farmentioning
confidence: 99%
“…As previous works suggested that the cooling timescale of coronal loops increases with greater loop length (e.g. Cargill et al 1995), some argued that the higher ELP loops are heated almost simultaneously with the lower loops but cool down much slower, resulting in prolonged EUV emission (Liu et al 2013;Masson et al 2017;Dai et al 2018;Chen et al 2020c). It has also been pointed out that the additional heating and extended cooling can be both at work in some ELP events (Sun et al 2013;Li et al 2014a), indicating that the two mechanisms are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%